Changing Identities of the Baltic States: Three Memories in Stone - Anna Gromilova (CES Working Papers, 2014)
This paper presents a comparative analysis of how Estonia, Latvia and Lithuania handled the process of nation-building, finding their self in their new reality which was no longer created and manipulated by the Soviets since their breakaway from the USSR. To do so, this paper suggests an ingenious method of the identity politics analysis which focuses on the importance of the so-called “lieux de mémoire” or “meaning-full places” for people. Monuments and statues are good examples of such places and play an important role in identity construction due to their ability to evoke particular kinds of feelings in people. Undertaking an in-depth analysis of monuments in Baltic States provides a valuable insight on the possibilities and challenges of Estonia, Lithuania and Latvia to develop communities of shared values and to finally stop living in the shade of their “post-Sovietness”.
Keywords: F5; Y8; 330; Monuments; national identity; Soviet Union; “Monument Wars”; Baltic States Romania